Developmental Profile and Diagnoses in Children Presenting with Motor Stereotypies - Cardona, Francesco; Valente, Francesca; Miraglia, Daniela; D’Ardia, Caterina; Baglioni, Valentina; Chiarotti, Flavia (Frontiers in Pediatrics, 2016)
Introduction: Motor stereotypies represent a typical example of the difficulty in distinguishing non-clinical behaviors (physiological and transient) from symptoms or among different disorders (“primary stereotypies”, associated with Autistic Spectrum Disorder (ASD), Intellectual Disabilities, genetic syndromes, sensory impairment). The aim of this study was to obtain an accurate assessment on the relationship between stereotypies and neurodevelopmental disorders. Methods: We studied 23 children (3 girls) aged 36 to 95 months, who requested a consultation due to the persistence or increased severity of motor stereotypies. None of patients had a previous diagnosis of ASD. The assessment included the Motor Severity Stereotypy Scale (MSSS), the Repetitive Behavior Scale-Revised (RBS-R), the Raven’s Colored Progressive Matrices (CPM), the Child Behavior Checklist for ages 1 ½ -5 or 4-18 (CBCL), the Social Responsiveness Scale (SRS) and the Autism Diagnostic Observation Schedule- Second edition (ADOS 2). Results: All patients were showing motor stereotypies for periods of time varying from 6 to 77 months. The MSSS showed each child had a limited number of stereotypies; their frequency and intensity were mild. The interference of stereotypies was variable; the impairment in daily life was mild. The RBS-R scores were positive for the subscale of “Stereotypic behaviors” in all children. Moreover, several children presented other repetitive behaviors, mainly “Ritualistic behavior” and “Sameness behavior.” All patients showed a normal cognitive level. The CBCL evidenced behavioral problems in 22% of the children: Internalizing problems, Attention and Withdrawn were the main complaints. On the SRS, all but one of the tested patients obtained clinical scores in the clinical range for at least one area. On the ADOS 2, four patients obtained scores indicating a moderate level of ASD symptoms, four had a mild level and fifteen showed no or minimal signs of ASD. Discussion: Motor stereotypies in children with normal cognitive level represent a challenging diagnostic issue for which a finely tailored assessment is mandatory in order to define a precise developmental profile. Thus, careful and cautious use of standardized tests is warranted to avoid misdiagnosis. Furthermore, it is hard to consider motor stereotypies, even the primary ones, exclusively as a movement disorder.